2020
DOI: 10.3390/nu12051238
|View full text |Cite
|
Sign up to set email alerts
|

Pyropia yezoensis Extract Suppresses IFN-Gamma- and TNF-Alpha-Induced Proinflammatory Chemokine Production in HaCaT Cells via the Down-Regulation of NF-κB

Abstract: Pyropia yezoensis, a red alga, is popular and harvested a lot in East Asia and is famous for its medicinal properties attributable to its bioactive compounds including amino acids (porphyra-334 and shinorine, etc.), polysaccharides, phytosterols, and pigments, but its anti-inflammatory effect and mechanism of anti-atopic dermatitis (AD) have not been elucidated. In this study, we investigate the anti-AD effect of P. yezoensis extract (PYE) on mRNA and protein levels of the pro-inflammatory chemokines, thymus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…It then induces the transcription of pro-inflammatory mediators such as iNOS and COX-2. Several studies have shown that anti-inflammatory agents inhibit NF-κB activation by preventing IκB degradation [ 19 , 20 , 21 ]. Thus, we attempted to determine whether 4H-7MTC inhibits IκB phosphorylation and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…It then induces the transcription of pro-inflammatory mediators such as iNOS and COX-2. Several studies have shown that anti-inflammatory agents inhibit NF-κB activation by preventing IκB degradation [ 19 , 20 , 21 ]. Thus, we attempted to determine whether 4H-7MTC inhibits IκB phosphorylation and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…P. yezoensis aqueous protein extract downregulated MAPK and NF-κB in the HK2 human proximal tubular epithelial cell line [152]; extracted MAAs obtained through an ethanol extraction, and reduced the expression of IL-1β, IL-6, IL-10, NF-κB in the skin of male ICR mice [153]. Other species can be included as containers of compounds which are able to inhibit NF-κB, including G. lanceolata [154], L. glandulifera [141], Polysiphonia morrowii [155], and Pyropia yezoensis [156]. In this latter study, the use of methanol extracts from P. yezoensis revealed TARC (thymus and activation-regulated chemokine) and MDC (macrophagederived chemokine) expression inhibition, ERK (extracellular signal-regulated kinase), JNK (c-Jun N-terminal kinase), p38 inhibition, and nuclear factors NF-κB and IkB-α downregulation, when using the cell line HaCaT induced with interferon (IFN)-γ and HaCaT induced with TNF-α [156].…”
Section: Anti-inflammatory Extracts and Compounds From Red Macroalgaementioning
confidence: 99%
“…Other species can be included as containers of compounds which are able to inhibit NF-κB, including G. lanceolata [154], L. glandulifera [141], Polysiphonia morrowii [155], and Pyropia yezoensis [156]. In this latter study, the use of methanol extracts from P. yezoensis revealed TARC (thymus and activation-regulated chemokine) and MDC (macrophagederived chemokine) expression inhibition, ERK (extracellular signal-regulated kinase), JNK (c-Jun N-terminal kinase), p38 inhibition, and nuclear factors NF-κB and IkB-α downregulation, when using the cell line HaCaT induced with interferon (IFN)-γ and HaCaT induced with TNF-α [156]. HaCaT are immortalized human skin keratinocytes that produce proinflammatory cytokines affecting the development of inflammatory skin disorders [119].…”
Section: Anti-inflammatory Extracts and Compounds From Red Macroalgaementioning
confidence: 99%
See 1 more Smart Citation
“…Pyropia yezoensis , rich in porphyran, is a kind of marine vegetable that is widely distributed and popular in China, Korea, and Japan. Studies have shown that porphyran derived from P. yezoensis demonstrates some pharmacological properties such as anti-inflammatory [ 27 ], antitumor [ 28 ], antioxidation, immunomodulation, anticardiovascular, and anticerebrovascular functions [ 29 ]; however, the lipid-lowering effect of P. yezoensis porphyran remains unclear. In this study, the yield of porphyran isolated from P. yezoensis via hot water extraction was optimized using response surface methodology (RSM) with a powerful statistical and mathematical model.…”
Section: Introductionmentioning
confidence: 99%